(untitled) (Italian Review of Legal History, 2021)
Approaching notarial production and uses in two different Italian communal cities, during the last medieval centuries, is a major way of highlighting specific declinations of a unique notarial civilization, that of Italian communal city-states. Considering the cities and their territories (“contadi”) as a whole, the essay first of all stresses the contadi sizes, their populations, the presence of towns and small villages, seen as the basical action field for the respective notaries. The second step consists in evaluating how much of the impressive notarial production for the two studied centuries is actually stored in the respective archives. Relatively known is the medieval documentation abundant loss trough the centuries, but the essay tries to estimate the remaining actual percentage, stressing the attention over the diplomatic sources weight, i.e. the parchments, wich form a particular type of notarial production, but nevertheless noteworthy. The third point of the article push forward an analysis of notarial careers, noting how much urban-centered they were in the two studied cities, more in Arezzo than in Milan. Is useful observing that the “contado” of the second was really full of notarial dinasties, scattered through the territory, not only in the Milanese little towns (“borghi”), but also in modest villages. The most important information concerns the different degrees of notarial career: in Arezzo only a step was considered enough, while in Milan normally notaries went trough a three step path: beginning with pronotarius, the professionist became notarius (laudatus ad omnia) and then iudex ordinarius. The complete unfolding of this path, nevertheless, is given only since the XIV century second half, when is possible to see it more frequently. The essay last part focuses about the notarial formulary, which reveals less differences than expected between the two cities. Among a common set of uses and practices two minor discrepancies catch the attention: Milanese notaries indicated very often a clause about the use prohibition of communal “carte debiti”, a sort of civic money substitute. That clause is normally absent in documents drawn up in Arezzo, revealing a different urban financing system. On the other hand the latter’s documents contain nearly always a different clause about the “preceptum guarentigie”, a communal law which permits immediate use of notarial debt documents, without court intervention. That clause also reveals a different debt legislation between the two cities. Nevertheless this two examples confirm the existence of a unique notarial civilization in Arezzo and Milan, declined somehow differently.